The Effects of Social Media in the Study Habit of 4th Year Criminology Students of Bestlink College, Bulacan Campus: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Due to technological advancement, students waste much of their study time using social media rather than dealing with academic issues. As a result, this study intended to investigate the effects of social media on the study habits of 4th-year Criminology students of Bestlink College, Bulacan Campus. The research design involved a questionnaire survey technique to collect data from a student population sample.  This study sought to examine the effects of social media on the study habits of 4th-year Criminology students of Bestlink College, Bulacan Campus. Nowadays, Social media is already taking all over the world. They use social media in many different ways. It is a big help, especially to the young generations, because social media are the product of technology and one way to do tasks easily. They consider it a part of our daily lives. Students love to use social media because it is fun, and they can express themselves through sharing and posting using Facebook and other social media that we can use.  The researchers utilized the descriptive research method since the focus of this study is considered salient features and trends that are developing on the Effect of Social Media in the Study Habit of 4th year Criminology Students, Bulacan Campus. According to Carague (2011), the Descriptive Method design clearly states what exists in the present study. This method involved gathering data about the variables. The respondents of the study consisted of fifty (50) 4th-year criminology students of Bestlink College, Bulacan Campus. A.Y 2021-2022. To get the needed data for the specific questions stated in the statement of the problem, the researchers used the random convenience sampling of research. The purposive sampling type was the most effective when one needs to study a certain cultural domain with the knowledge of experts within. The researchers used purposive sampling in the selection of their respondents.  The study concluded that based on the respondent's profile of 4th-year criminology students of Bestlink College, Bulacan Campus, were 22-24 years old, Male with a Civil Status of Single. The respondents agree that social media negatively impacts mental health and influences their behaviour and actions. The respondents agree that social media negatively and positively affected the study habits of 4th-year criminology students of Bestlink College, Bulacan Campus. The respondents Agree with the given solution to be mindful of your social media habits, Set limits on the amount of time you spend on social media, Know when it's time to stop scrolling, use social media to connect with people who inspire you, and provide a sense of belonging and Spend less time on social media platforms. The main purpose of this research is to find out the effect of social media on the study habits of 4th-year criminology students and also to find out the negative and positive effects of social media on criminology students.